Aryl-Substituted Dihydro-Pyrimidines Effecting Kinesin Eg5 as Novel Approach for Cancer Treatment - Dialekti Chlorou; Eleni Pontiki (Molecules)
Cancer is one of the most lethal diseases of this century. Unfortunately, many anticancer agents have harsh side effects or fail to work against cancer any longer due to tolerance. Dihydropyrimidinones are promising structures containing a pyrimidine ring. Targeting Eg5 is their most well-known activity. Inhibition of this enzyme gives them the privilege of strong cytotoxic activity with less side effects. Phenyl ring is a group that can be found in the majority of organic molecules and possesses preferable pharmacokinetic and pharmacodynamic characteristics. This review studies DHPM derivatives that are substituted with a phenyl ring and possess antiproliferative ability by inhibiting Eg5. The compounds are able to inhibit different cancer cell lines, and some are more potent than the standard drug. The biological results are in accordance with the docking studies.